2021
DOI: 10.1111/exsy.12895
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast enhanced‐magnetic resonance imaging radiomics combined with a hybrid adaptiveneuro‐fuzzyinference system‐particle swarm optimization approach for breast tumour classification

Abstract: The authors propose a method for breast dynamic contrast enhanced‐magnetic resonance imaging classification by combining radiomic texture analysis with a hybrid adaptive neuro‐fuzzy inference system (ANFIS)‐particle swarm optimization (PSO) classifier. The fast discrete curvelet transform is utilized as a decomposition scheme in multiple scales. The mean and entropy features extracted from the produced scheme are used as texture descriptors. Principal component analysis (PCA) involves reduction of the dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…We have considered the classifier with the best results as the best performer. Mubarak et al [ 9 ] provide instant access to a variety of classification techniques, such as KNN, SVM, LDA [ 39 ], LR [ 40 ], DT [ 41 ], and NB [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have considered the classifier with the best results as the best performer. Mubarak et al [ 9 ] provide instant access to a variety of classification techniques, such as KNN, SVM, LDA [ 39 ], LR [ 40 ], DT [ 41 ], and NB [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…A more advanced approach is utilizing Curvelet Transform (CT) as a feature extraction method for its ability to obtain both linear and curved edges along multiple scales and orientations [42]. In this regard, several studies have applied CT in various computer vision tasks, namely tumor detection [43], [44], image segmentation [45], [46], [47], signature verification [48], [49], and face recognition [50], [51], [52]. However, despite its advantages, limited number of studies have reported using CT as a feature extraction tool for AD detection using MRI images [53], [54].…”
Section: Introductionmentioning
confidence: 99%